Critical Causes and Consequences of Construction Project Interruption: Client, Contractor, Consultant and External Factors Standpoints - Mohamed Alias, Nurbasirah; Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2013)
It should be pointed out that the dilemma of interruption and stoppage in the construction industry is a large-scale trend. Construction interruption and stoppage is considered one of the most recurring problems in the construction industry. Construction Interruption and stoppage is always measured as costly to all parties concerned in the projects and very often it will result in clash, claims, total desertion and much difficult for the feasibility and it slows the growth of construction sector. The objective of the research work that underpins this paper was to investigate the Factors and Consequences of construction projects on local contractors. A construction project is commonly acknowledged as successful when the aim of the project is achieved in terms of predetermined objectives that are mainly completed the project on time, within budget and specified quality in accordance with the specifications and to stakeholders’ satisfaction. One of the most important problems that may arise in the construction project is delays and the magnitude of these delays varies considerably from project to project. According to delay categories that were contractor related, client related, consultant related, labour related and external related, the study revealed the six major effects of delay that were time overrun, cost overrun, dispute, arbitration, total abandonment, and litigation.